Suppressive effects of Mimosa pudica (L.) constituents on the production of LPS-induced pro-inflammatory mediators - Patel, Neeraj K.; Bhutani, Kamlesh K. (Technische Universität Dortmund, 2014)
The present study deals with the isolation of fourteen compounds from the active ethyl acetate (MPE) extract of M. pudica (L.) whole plant and their subsequent evaluation for the nitric oxide (NO), tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (IL-1β) inhibitory activities in lipopolysaccharide (LPS) stimulated RAW 264.7 and J774A.1 cells. Among the tested compounds, L-mimosine (12; IC50= 19.23 to 21.15 μM), crocetin (4; IC50= 23.45 to 25.57 μM), crocin (14; IC50= 27.16 to 31.53 μM) and jasmonic acid (11; IC50= 21.32 to 29.42 μM) were identified as potent NO inhibitor when tested on the macrophages. Similarly, towards TNF-α and IL-1β inhibition, including these four compounds, and ethyl gallate (3), gallic acid (10) and caffeic acid (7) were found to be more active with half maximal concentration, 17.32 to 62.32 μM whereas the other compounds depicted moderate and mild effects (IC50= 59.32 to 95.01 μM). Also, at a dose of 40 mg/Kg, L-mimosine (12), jasmonic acid (11), crocin (14) and its de-esterified form, crocetin (4) were found to significantly (p < 0.05 and 0.001) reduce 60.7 %, 48.9 %, 48.4 % and 43.6 % respectively of TNF-α production in female Sprague Dawley rats. However, in case of IL-1β, with the same dose (40 mg/Kg), jasmonic acid (11) exhibited significant reduction with 54.2 % followed by crocin (14) (50.2 %) and crocetin (4) (39.8 %) while L-mimosine (12) was found to reduce only 16.3 %. Based on the results, it can be estimated that these compounds imparting greatly to anti-inflammatory effects of M. pudica in vitro as well as in vivo through reduction of LPS-induced pro-inflammatory mediators which affirm the ethno-pharmacological use of this plant for prevention of inflammatory-related disorders.
EXCLI Journal ; Vol. 13, 2014
Keywords: Mimosa pudica; L-mimosine; crocin; crocetin; jasmonic acid; inflammation; 610